The betrayal of Thomas True / A.J. West. - West, A. J. (Orenda Books, 2024)
Set in the buried streets of Georgian London and the outrageous underworld of the molly houses, a carpenter hiding a double life searches for a traitor who is betraying the secrets of the mollies.